From the Field into the Lab: Contribution of Traditional Knowledge to Modern Medicine - Uprety, Yadav; Datta Bhattarai, Hari (Annapurna Journal of Health Sciences, 2023)
The contribution of traditional knowledge to modern medicine has been recognized as it provides valuable clues to the scientific community for drug discovery. Although western science was reluctant to recognize its contribution until recently, there is growing interest in traditional knowledge in recent years. There are well-established cases of traditional knowledge from around the world that have led to drug discovery. There is also a huge potential to explore this area in Nepal. In this short communication, we discussed some examples of traditional knowledge that are the source of clues for drug discovery, and also discussed the prospects of traditional knowledge and bioprospecting in Nepal. We hope that this brief article is of interest to readers outside the traditional knowledge and biodiversity domain.